Glyceryl trinitrate for the treatment of ischaemic stroke: Determining efficacy in rodent and ovine species for enhanced clinical translation. Issue 12 (December 2021) - Sorby-Adams, Annabel J; Learoyd, Annastazia E; Bath, Philip M; Burrows, Fiona; Farr, Tracy D; Leonard, Anna V; Schiessl, Ingo; Allan, Stuart M; Turner, Renée J; Trueman, Rebecca C
Hypertension is a leading risk factor for death and dependency after ischaemic stroke. However, administering anti-hypertensive medications post-stroke remains contentious with concerns regarding deleterious effects on cerebral blood flow and infarct expansion. This study sought to determine the effect of glyceryl trinitrate (GTN) treatment in both lissencephalic and gyrencephalic pre-clinical stroke models. Merino sheep underwent middle cerebral artery occlusion (MCAO) followed by GTN or control patch administration (0.2 mg/h). Monitoring of numerous physiologically relevant measures over 24 h showed that GTN administration was associated with decreased intracranial pressure, infarct volume, cerebral oedema and midline shift compared to vehicle treatment (p < 0.05). No significant changes in blood pressure or cerebral perfusion pressure were observed. Using optical imaging spectroscopy and laser speckle imaging, the effect of varying doses of GTN (0.69–50 µg/h) on cerebral blood flow and tissue oxygenation was examined in mice. No consistent effect was found. Additional mice undergoing MCAO followed by GTN administration (doses varying from 0–60 µg/h) also showed no improvement in infarct volume or neurological score within 24 h post-stroke. GTN administration significantly improved numerous stroke-related physiological outcomes in sheep but was ineffective in mice. This suggests that, whilst GTN administration could potentially benefit patients, further research into mechanisms of action are required.